Impact of Aging in Microglia-Mediated D-Serine Balance in the CNS. (27th September 2018) - Beltrán-Castillo, Sebastián; Eugenín, Jaime; von Bernhardi, Rommy
Abstract : A mild chronic inflammatory state, like that observed in aged individuals, affects microglial function, inducing a dysfunctional phenotype that potentiates neuroinflammation and cytotoxicity instead of neuroprotection in response to additional challenges. Given that inflammatory activation of microglia promotes increased release of D-serine, we postulate that age-dependent inflammatory brain environment leads to microglia-mediated changes on the D-serine-regulated glutamatergic transmission. Furthermore, D-serine dysregulation, in addition to affecting synaptogenesis and synaptic plasticity, appears also to potentiate NMDAR-dependent excitotoxicity, promoting neurodegeneration and cognitive impairment. D-serine dysregulation promoted by microglia could have a role in age-related cognitive impairment and in the induction and progression of neurodegenerative processes like Alzheimer's disease.